(untitled) (Research, Society and Development, 2022)
Objective: We aimed at investigating and describing the drug and material resources in health shortage in the Brazilian services during the COVID-19 pandemic. Methods: We conducted a cross-sectional study in the format of an online survey with closed questions. Information was sought about the institutional and care profile, pharmaceutical service organization, non-compliance in the stock, or lack of drugs and other health products between April and October 2020. We performed descriptive, univariate, and multivariate statistical analyses, such as Fisher’s t-test, chi-square test, and the Multiple Correspondence and Hierarchical Cluster analyses. A p-value below 0.05 and a 95% significance level were considered. Results: 228 Brazilian institutions, most located in the capital cities, with specific beds for COVID-19 and public administration, were included in the study. Grouping by similarity separated the study sample into five heterogeneous clusters. Eighty-four percent of the services indicated a drugs shortage, especially neuromuscular blocking agents (64.9%), hypnotics and sedatives (52.9%), vasoactive drugs (37.3%), and antiinfective agents (30%). Conclusion: In all the clusters, there were reports of a shortage of items considered essential in the management of critically-ill patients, corroborating the perception that this was a significant challenge for pharmaceutical assistance in various Brazilian services during the COVID-19 pandemic.